2019
DOI: 10.3390/catal9060538
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Bimetallic Cu–Ni Nanoparticle-Supported Catalysts in the Selective Oxidation of Benzyl Alcohol to Benzaldehyde

Abstract: Three bimetallic Cu–Ni nanoparticle-supported catalysts were synthesized by co-immobilization followed by H2 reduction. A chromium(III) terephthalate metal organic framework (MIL-101), titanium dioxide (TiO2), and carbon (C) with different properties (acidity and Brunauer–Emmett–Teller surface area) were selected as supports for studying the effect of the support nature on the catalytic activity and selectivity in the oxidation of benzyl alcohol. The physicochemical properties of the Cu–Ni-supported catalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…There are different advantages depending on the metal combination, and there are even advantages to not using precious metals. It has recently been shown that bimetallic site catalysts can also be applied with TiO 2 [160]. However, this approach requires more research of bimetal sites.…”
Section: Discussionmentioning
confidence: 99%
“…There are different advantages depending on the metal combination, and there are even advantages to not using precious metals. It has recently been shown that bimetallic site catalysts can also be applied with TiO 2 [160]. However, this approach requires more research of bimetal sites.…”
Section: Discussionmentioning
confidence: 99%
“…69 The MIL-101(Cr)-supported catalysts were synthesized through coimpregnation followed by H 2 reduction. 52,70 First, 24.0 mg of HAuCl 4 $4H 2 O and 7.0 mg of Pd(CH 3 COO) 2 were melted in 1 mL of ethanol. Subsequently, the mixture solution of HAuCl 4 $4H 2 O and Pd(CH 3 COO) 2 was added slowly dropwise into MIL-101(Cr) (0.5 g).…”
Section: Preparation Of the Catalystsmentioning
confidence: 99%
“…S7 †). 70 The TEM micrograph and Au-Pd size distribution for the reused Au(2)Pd(1)/MIL-101(Cr) catalyst were presented in Fig. S8.…”
Section: Reusability Of Catalystsmentioning
confidence: 99%
“…In addition, the nature of the nanoparticles support can have a significant influence on their catalytic performance. This aspect is addressed in several papers of this section [1,2].…”
mentioning
confidence: 99%
“…The challenging selective oxidation of alcohols to the corresponding carbonyl compounds through sustainable catalytic procedures was addressed by Liu et al [2] focusing on selective oxidation of benzyl alcohol to benzaldehyde, using molecular oxygen as the oxidizing agent. In total, three bimetallic Cu-Ni nanoparticle-supported catalysts were synthesized by co-immobilization followed by H 2 reduction.…”
mentioning
confidence: 99%